Determination of herbicides residues in soil by small scale extraction - Polese, Luciana; Dores, Eliana Freire Gaspar de Carvalho; Jardim, Elaine Fátima Galatti; Navickiene, Sandro; Ribeiro, Maria Lúcia (Eclética Química, 2002)
Herbicides such as trifluralin, simazine, atrazine, metribuzin and metolachlor are used in Brazilian agriculture. The efficiency of a small scale method for determination of these herbicides and two degradation products (deisopropylatrazine and deethylatrazine) in soil samples was evaluated. The compounds were extracted from soil samples (5 g) with 20 ml of ethyl acetate in a mechanical shaker for 50 min. Following the extraction, the supernatant was dried through anhydrous sodium sulphate, concentrated and analysed by high resolution gas chromatography (HRGC) with thermionic specific detection (TSD). Mean recoveries obtained from soil samples fortified at three different levels ranged from 81 to 115% with relative standard deviation (RSD) values varying from 1.2 to 12.7%. The method detection limits ranged from 0.01 to 0.06 mg kg-1. The methodology was applied using soil samples from farms located near the town of Araraquara, in the State of São Paulo, Brazil.